Evaluating common weight training concepts associated with developing muscular strength: Truths or myths? - Hales, M. (Strength and Conditioning Journal, 2011)
This article describes several strength training concepts and assesses those using pertinent biomechanical and physiological principles. Because maximizing muscular strength is extremely important to the outcome in certain athletic competitions, much of the discussion will focus on one sport in particular: Powerlifting. However, any sport that places high demand on increased strength levels could benefit as well. A challenge that strength and conditioning professionals may encounter with regards to any type of exercise programs is discerning which training methods or concepts are counterproductive (myths) and which are beneficial (truths).